2021
DOI: 10.3390/jcm10102092
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Torque Teno Virus (TTV) in HIV/HCV Coinfected and HCV Monoinfected Patients Treated with Direct-Acting Antiviral Therapy

Abstract: Torque Teno virus (TTV) is a ubiquitous virus that causes chronic infection in humans with unknown clinical consequences. Here, we investigated the influence of TTV infection on HCV direct-acting antiviral (DAA) efficacy in HIV/HCV coinfected and HCV monoinfected patients as controls. Of 92 study patients, 79.3% were TTV DNA positive; untreated patients exhibited a significantly higher proportion of TTV DNA-positivity vs. sustained virological response (SVR) patients (100.0% vs. 65.2%, p < 0.001), while TTV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…Torque teno virus (TTV) had a higher viral burden in HIV+ people. Of interest, TTV has an increased viremia in HIV+ patients [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Torque teno virus (TTV) had a higher viral burden in HIV+ people. Of interest, TTV has an increased viremia in HIV+ patients [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The high circulation of this virus among the human population indicates that TTV is not the main cause of a specific disease. Still, TTV can help develop a disease as an auxiliary factor or cofactor [ 34 ]. It has been shown that TTV viral replication and, thus, viral load is significantly increased in patients with pathological conditions such as untreated solid cancer [ 96 ].…”
Section: Human Cancermentioning
confidence: 99%
“…Its high prevalence in human populations indicates that this virus cannot be the leading cause of a particular disease. Still it has the ability to act as an auxiliary factor in the initiation and development of the disease [ 34 , 35 ]. Fewer studies have been conducted on TTMV and TTMDV, but it is known that the prevalence of these viruses in human blood is significantly lower than in TTV [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genomic region analyzed in this study, as well as in another recent study [ 35 ], proves to have a higher phylogenetic resolution, as it is able to discriminate between TTV subspecies, defined as a grouping of isolates with ORF1 nucleotide sequence divergence of 35-20% [ 9 ]).…”
mentioning
confidence: 99%